Saúde e energia: (as)simetrias na promoção de territórios saudáveis no Rio Grande do Norte - Correia, Laís Ariane Martins Barbosa (2023)
This thesis highlights the importance of promoting health both for the biological body and for the dignity and development of human potential and presents its spatial approach, translated by the designation of Healthy Territories, as a valuable indicator of sustainability in assessments of territorial impacts, specifically, of the wind energy production activity. Conceiving Health in a multifactorial way, this thesis starts from the premise that it is not enough to enable the use of high potential renewable energy as a solution for the supply of electricity, without thinking about combining it with the territory, materializing solutions that promote health and well-being to populations. Given this panorama, the thesis requires a theoretical construction in which the concepts of Territory, Health and Energy are considered from their interfaces, with Sustainability as a backdrop. Therefore, Healthy Territory and renewable energy appear as perspectives for providing socio-environmental quality to society and are aligned, from a Sustainability point of view, with the social, economic and environmental context of the territory as a resource, guaranteeing the achievement of private interests, and as a shelter, based on the development of strategies that guarantee survival in the places. Therefore, this thesis aims to understand the relationship between wind energy production and the promotion of a Healthy Territory in the communities Amarelão, Serrote de São Bento, Santa Terezinha Settlement and Enxu Queimado, in Rio Grande do Norte, and proposes, as a methodological tool, a matrix of analysis based on space elements. It employs bibliographic, documentary and field research from the perspective of a case study, characterized as exploratory, descriptive and explanatory research with a predominantly qualitative approach to data analysis, generated through the application of a research form, focus group and semi-structured interviews, in addition to the collection of secondary data. The research results reflect the dialectic of reality: on the one hand, it ratifies the hypothesis that the production of wind energy results in shortrange benefits for the well-being of local populations – notably in Enxu Queimado. But, on the other hand, it highlights the strength of the people who inhabit the territory in the struggle for recognition of their way of living and using it, which drove collaboration between Firms and Men, mediated by Institutions, in providing conditions for permanence in the living territory – such as ensuring access to quality water through the installation of a desalination plant that serves the communities of Amarelão, Serrote de São Bento and Santa Terezinha Settlement. The use of the matrix of space elements as a methodological tool, in turn, proved to be methodologically effective and operationally didactic for processing data and evaluating how men, firms and institutions articulate themselves in an environment equipped with infrastructure to, in the work under analysis, enable the promotion of Healthy Territories in areas of wind energy production. Thus, starting from the analysis of the parts to the reading of the whole, the assessment matrix for the elements of space presented in the thesis constitutes a methodological reading key that can be applied to various themes, since it is based on reading the totality from elements that are inherent to it. Furthermore, the production of the thesis revealed a fruitful research agenda, with new questions that demand a deeper understanding both in the theoretical and methodological aspect, and in the daily lives of the people who live and use the territory, with a view to expand the comprehension of the relationship between wind energy production and the promotion of Healthy Territory in the semiarid region.